Efficacy of Topical Coffee Paste to Collagen Density in Wistar Rats Incision Wound - Debby Handayati Harahap; Fifa Argentina; Yuli Kurniawati; Citra Tresna Murti; Yudha Dwi Satrio (HM Publisher, 2018)
Background :Collagen plays a very important role in humans at every stage of wound healing. Coffee contains many antioxidants that stimulate the formation of collagen dermis by increasing the production of Tissue Inhibitor of Matrix Metalloproteinas-1 in the dermis that serves to inhibit the breakdown of collagen. This study aims to determine the efficacy of topical pasta coffee to collagen density. Methods: Experimental Laboratories Study with pre and post test controlled group design research was undertaken from September to November 2017 at Animal House and Dyatnitalis Laboratory, Palembang. 30 male white rats of wistar strain were divided into 5 groups then performed 2 cm dermal incision and giving various concentration of coffee paste. On the day 0 and 5th after coffee paste, the percentage of collagen density is checked. The efficacy of coffee paste was analyzed by Paired T Test/Wilcoxon while the comparison of efficacy was analyzed by Independent T Test / Mann Whitney then continued with One Way ANOVA Test and Tukey test. Data analysis using SPSS version 18.0. Results: There was an average difference of percentage level of collagen density before and after vitamin C (p = 0,003), coffee paste 20% (p = 0,043), coffee paste 40% (p = 0,045) and coffee paste 80% (p = 0,011) . In addition, there was an average difference of percentage of collagen density between negative control group with positive control group and 40% coffee paste. From the results of Post Hoc test results showed that there was a difference of percentage of collagen density of negative control group with coffee paste group 40%. Conclusion: There is efficacy of topical coffee paste on collagen density in various concentrations where the highest increase of collagen density is 246,96% after coffee paste 40%. Keyword: Coffee Pasta, Collagen, Injured Incision, Vitamin C